Extraction of naphthenic acids from acidic petroleum crude oil utilizing 2-methylimidazole with the aid of Ca/Al2O3 and Ce/Al2O3 catalysts / Norshahidatul Akmar Shohaimi ... [et al.] - Shohaimi, Norshahidatul Akmar; Wan Abu Bakar, Wan Azelee; Mohd Shukri, Nurasmat; Shaidi, Amier Khairan (2019)
Naphthenic acids (NAs) is one of the major sources of corrosion in oil pipelines and distillation units in crude oil refineries. Removing NA compounds from crude oils is regarded as one of the most crucial processes in heavy oil upgrading. Catalytic deacidification method had been developed in order to reduce the total acid number values in crude oil. Crude oil from Petronas Penapisan Melaka had been chosen to be studied with original total acid number (TAN) of 2.43 mg KOH/g. The parameters used were different catalyst calcination temperatures, catalyst loading, reagent concentration, reaction times and reaction temperature. Acid removal agent of 2-methylimidazole in ethanol and monometallic calcium and cerium doped with alumina were used as a catalyst. The results showed that with the aid of catalyst, the TAN can be reduced to lower than 1 mg KOH/g. Catalyst of Ca/Al2O3 calcined at 900oC gave a better reduction than Ce/Al2O3 with 83.54% of TAN reduction (2.43 to 0.4) for Ca/Al2O3 catalyst and 71.19% (2.43 to 0.7) for Ce/Al2O3 catalyst. The best catalyst underwent several characterization methods such as X-Ray Diffraction Spectroscopy (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetry Analysis (TGA-DTA) for its physicochemical properties. It can be concluded that catalytic deacidification method was effective in extracting NAs from the crude oil thus lowered the TAN value to less than 1 mg KOH/g.